儿科皮肤病专家和风湿病专家对 CLASI 的评估. (2nd January 2019) - Kushner, C.J.; Tarazi, M.; Gaffney, R.G.; Feng, R.; Ardalan, K.; Brandling‐Bennett, H.A.; Castelo‐Soccio, L.; Chang, J.C.; Chiu, Y.E.; Gmuca, S.; Hunt, R.D.; Kahn, P.J.; et al.
Abstract : Linked Article: Kushner et al. Br J Dermatol 2019;180 :165–171